An Investigation into Academic Vocabulary Difficulties in Speaking of EFL University Students in the English Education Program - Assa Jidah; Fatin Nadifa Tarigan (Association of Language Teachers in Southeast Asia (ALTSA), 2025)
This study investigates the difficulties faced by EFL university students in using academic vocabulary during speaking tasks. Conducted with undergraduate students of the English Education Program at Universitas Pembinaan Masyarakat Indonesia, the research employed speaking tasks, questionnaires, and interviews to collect data. Thematic analysis and descriptive statistics were used to examine students’ productive use of academic vocabulary, focusing on collocations, pronunciation, lexical range, and confidence. The findings revealed that remembering and applying collocations (72%) and pronouncing academic terms (65%) were the most common problems. More than half of the students also reported low confidence (58%) and limited lexical knowledge (50%), with only a small proportion (15%) expressing overall confidence in their academic vocabulary use. These results highlight a persistent gap between receptive and productive knowledge, as students often recognized academic vocabulary in texts but struggled to apply it in oral communication. The study concludes that targeted pedagogical strategies, including explicit collocation practice, pronunciation support, and confidence-building activities, are needed to strengthen students’ academic oral proficiency and prepare them for academic and professional contexts.